UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR PRODUK INDUSTRI MAKANAN DAN MINUMAN KE KOREA SELATAN TAHUN 2014-2019 - Metrina Veni; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The food and beverage industry is one of 5 sectors focused on development by the Indonesian government, because it has a big influence on the country's economic growth. So the food and beverage industry is included in "Making Indonesia 4.0". South Korea is one of Indonesia's export destinations because it is considered to have a great opportunity. The complementary nature of each country's resources and excellence makes the economic and political processes that occur generate great cooperation opportunities This qualitative research uses the perspective of liberalism and is analyzed using the theory of cooperation with the level of state analysis. Data comes from books, journals, news, documents from several ministries, articles, and websites. Based on the big influence of the food and beverage industry for Indonesia, as well as the large opportunities for export to South Korea, the Indonesian government made various efforts to maximize its exports, among others through improving cooperation with South Korea, improving product quality, and product introduction through various exhibitions and social media.  Keywords: Efforts, Exports, Influences, Food and Beverages Product, Indonesia Goverment, South Korea